Sleep quality and related factors among healthcare workers in designated quarantine hospital site in post-pandemic based on the health ecological model: a cross-sectional study in Nanjing, China - Zhou, Han; Shen, Lei; Tan, Huafeng; Zhou, Jiefang; Zheng, Qiyi; Jiang, Dongdong (Frontiers in Public Health, 2024)
Aims: This study aims to assess the status and related factors among healthcare workers (HCWs) in designated quarantine-hospital-site (DQHS) based on the model of health ecology.: The cross-sectional study was conducted from April to May, 2022, which included 351 valid samples. We measured sleep quality byusing the Pittsburgh Sleep Quality Index, which encompasses seven dimensions: subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleep medication, and daytime dysfunction. Each dimension is scored individually, contributing to an overall sleep quality score. Factors associated with the sleep quality of HCWs in DQHS were divided into individual, behavioral, interpersonal and social dimensions. Hierarchical linear regressions were conducted to identify the potential factors associated with sleep quality among HCWs in DQHS.Results: HCWs in DQHS had a statistically higher sleep quality than the Chinese national normThe sleep quality of HCWs in DQHS was statistically higher than Chinese national norm. HCWs who were female, afraid of Coronavirus disease, had more negative emotions, frequently worked overtime, were married, and had a higher income were more likely to experience worse sleep quality (p< 0.05), while those who worked between 51 and 70 hours weekly, treated over 10 patients daily, and engaged in more health behaviors may have better sleep quality HCWs who are female, afraid of Coronavirus disease, had more negative emotions, frequently working overtime, married and had higher income were more likely to experience worse sleep quality (p< 0.05), while those had worked between 51 and 70 hours weekly, treated over 10 patients daily, and conducted more health behaviors may have better sleep quality (p< 0.05).This study revealed a worrying status level of sleep quality among HCWs in DQHS. The government, hospital managers, and families should collaborate to ensure the sleep quality of HCWs in DQHS. Joint efforts from the multiple parties (government, hospital managers, families) should be taken to assure the sleep quality of HCWs in DQHS.